Bells of San Angelo - Witney, William, 1915-2002; Rogers, Roy, 1911-1998; Rogers, Dale Evans; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Production, 1947)
Gridley is mining silver from an old Mexican mine and bringing it into the USA through a passage into his worthless mine. Border guard Rogers suspects Gridley and finally finds the secret entrance to the Mexican mine. He sends Lee Madison for help, only to have her captured by Gridley. Trigger brings help that takes care of Gridley's men, and now Roy has to rescue Madison. --
Roy Rogers, Dale Evans, Andy Devine, Bob Nolan.
Director of photography, Jack Marta; editor, Les Orlebeck.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Smugglers -- Mexican-American Border Region -- Drama; Silver mines and mining -- Mexican-American Border Region -- Drama; Border patrols -- Mexican-American Border Region -- Drama; Western films; Action and adventure films; Feature films; Fiction films; Internet videos; Streaming video